Unveiling the startup characteristics of pump as turbine using computational and experimental techniques - Dessie Tarekegn Bantelay; Girma Gebresenbet; Bimrew Tamrat Admasu; Muluken Temesgen Tigabu; Muluken Zegey Getie (Results in Engineering)
Over time, the interest in using pumps as turbines (PATs) instead of conventional turbines has increased. The nature and operation challenges of hydraulic resources necessitate frequent starts and stops, resulting in severe fluctuations caused by fluid flow that led to machine deterioration. Gaining more insight into how the flow develops during transients allows for safe operating conditions, effective production planning, and estimating the cost variation due to operational changes. Currently, there are limited studies on the properties of pumps that function as turbines (PATs) at startup. This work analyzes the PAT's transient behavior over time while the system is starting up. A test rig was constructed for the centrifugal PAT to reveal its transient characteristics during the start-up process. In addition to the experiments, flow-dynamic simulations were run using ANSYS-Fluent. The rotating part's angular velocity was validated against experimental data. Transient characteristics such as the flow rate, head, torque, and tangential force of the PAT, etc., as well as the internal flow during the start-up, were analyzed. During the start-up transient phase, the transient characteristic parameters such as pump rotational speed, head, and flow rate change significantly. As the rotating speed approaches the rated speed, there is an increase in the transient impact head to a peak that is 2.04 times that of the rated head. The numerical simulation's outcomes and the experimental data were in excellent agreement.